2013
DOI: 10.3390/f4030575
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Improvement of White Spruce Mechanical Wood Traits—Early Screening by Means of Acoustic Velocity

Abstract: There is a growing interest to use acoustic sensors for selection in tree breeding to ensure high wood quality of future plantations. In this study, we assessed acoustic velocity as a selection trait for the improvement of mechanical wood properties in two 15-and 32-year-old white spruce (Picea glauca [Moench.] Voss) genetic tests. Individual heritability of acoustic velocity was moderate and of the same magnitude as heritability of wood density. Considerable genetic gain could be expected for acoustic velocit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
61
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 39 publications
10
61
4
Order By: Relevance
“…In addition, these stands were analysed for SWV and SWV and was found to be significantly positively correlated to height and DBH. A similar correlation was also found by El-Kassaby et al [45], Lenz et al [12], Li et al [46], Ratcliff et al [47] and Wielinga et al [48].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In addition, these stands were analysed for SWV and SWV and was found to be significantly positively correlated to height and DBH. A similar correlation was also found by El-Kassaby et al [45], Lenz et al [12], Li et al [46], Ratcliff et al [47] and Wielinga et al [48].…”
Section: Discussionsupporting
confidence: 84%
“…Similar negative correlations were found in numerous other species [9]; however, because correlations between growth and wood quality traits were found to vary among subpopulations and families, this variation allows for simultaneous improvement of both traits [10]. Thus, consideration of wood quality parameters in tree improvement programs is necessary to produce raw material with well-defined structural properties [11,12].…”
Section: Introductionmentioning
confidence: 67%
“…This indicates that tree breeders can reliably select high stiffness Norway spruce trees for breeding purpose using the two nondestructive methods (Pilodyn penetration and acoustic velocity) on standing trees. Moderate or high genetic correlations between MOE and acoustic velocity have also been reported in other conifers (Auty and Achim 2008;Kennedy et al 2013;Lenz et al 2013).…”
Section: Predictability Of Wood Density Mfa and Moe Using Pilodyn Pmentioning
confidence: 73%
“…Direct measurement using microscopy on individual fiber is extremely time-consuming and expensive, and the representativity of the results is disputable unless a very large number of fibers are analyzed. It has been reported that acoustic velocity (AV) measured with Hitman ST 300 device could be an efficient indirect method for estimation MFA (Grabianowski et al 2006;Li et al 2007;Lenz et al 2013).…”
mentioning
confidence: 99%
“…Most of the genetic variation studies in Malawi have focused on growth traits [2]. However, faster growth is generally negatively correlated with important wood quality traits [15,16]. Therefore, there is a need to include wood quality traits in tree selection programmes to ensure future wood supplies have the appropriate mechanical properties for structural applications and other end uses.…”
Section: Introductionmentioning
confidence: 99%